---------------------------------------------------------------------------------------------------- --- Copyright (c) 2014 Parikshit Khanna. All rights reserved. --- Released under Apache 2.0 license as described in the file LICENSE. --- Authors: Parikshit Khanna, Jeremy Avigad ---------------------------------------------------------------------------------------------------- -- Theory list -- =========== -- -- Basic properties of lists. import tools.tactic import data.nat import logic -- import if -- for find using nat using eq_ops namespace list -- Type -- ---- inductive list (T : Type) : Type := | nil {} : list T | cons : T → list T → list T infix `::` : 65 := cons section variable {T : Type} theorem list_induction_on {P : list T → Prop} (l : list T) (Hnil : P nil) (Hind : forall x : T, forall l : list T, forall H : P l, P (cons x l)) : P l := list_rec Hnil Hind l theorem list_cases_on {P : list T → Prop} (l : list T) (Hnil : P nil) (Hcons : forall x : T, forall l : list T, P (cons x l)) : P l := list_induction_on l Hnil (take x l IH, Hcons x l) notation `[` l:(foldr `,` (h t, cons h t) nil) `]` := l -- Concat -- ------ definition concat (s t : list T) : list T := list_rec t (fun x : T, fun l : list T, fun u : list T, cons x u) s infixl `++` : 65 := concat theorem nil_concat (t : list T) : nil ++ t = t := refl _ theorem cons_concat (x : T) (s t : list T) : (x :: s) ++ t = x :: (s ++ t) := refl _ theorem concat_nil (t : list T) : t ++ nil = t := list_induction_on t (refl _) (take (x : T) (l : list T) (H : concat l nil = l), show concat (cons x l) nil = cons x l, from H ▸ refl _) theorem concat_assoc (s t u : list T) : s ++ t ++ u = s ++ (t ++ u) := list_induction_on s (refl _) (take x l, assume H : concat (concat l t) u = concat l (concat t u), calc concat (concat (cons x l) t) u = cons x (concat (concat l t) u) : refl _ ... = cons x (concat l (concat t u)) : { H } ... = concat (cons x l) (concat t u) : refl _) -- Length -- ------ definition length : list T → ℕ := list_rec 0 (fun x l m, succ m) theorem length_nil : length (@nil T) = 0 := refl _ theorem length_cons (x : T) (t : list T) : length (x :: t) = succ (length t) := refl _ theorem length_concat (s t : list T) : length (s ++ t) = length s + length t := list_induction_on s (calc length (concat nil t) = length t : refl _ ... = zero + length t : {symm (add_zero_left (length t))} ... = length (@nil T) + length t : refl _) (take x s, assume H : length (concat s t) = length s + length t, calc length (concat (cons x s) t ) = succ (length (concat s t)) : refl _ ... = succ (length s + length t) : { H } ... = succ (length s) + length t : {symm (add_succ_left _ _)} ... = length (cons x s) + length t : refl _) -- add_rewrite length_nil length_cons -- Append -- ------ definition append (x : T) : list T → list T := list_rec [x] (fun y l l', y :: l') theorem append_nil (x : T) : append x nil = [x] := refl _ theorem append_cons (x : T) (y : T) (l : list T) : append x (y :: l) = y :: (append x l) := refl _ theorem append_eq_concat (x : T) (l : list T) : append x l = l ++ [x] := refl _ -- add_rewrite append_nil append_cons -- Reverse -- ------- definition reverse : list T → list T := list_rec nil (fun x l r, r ++ [x]) theorem reverse_nil : reverse (@nil T) = nil := refl _ theorem reverse_cons (x : T) (l : list T) : reverse (x :: l) = append x (reverse l) := refl _ theorem reverse_singleton (x : T) : reverse [x] = [x] := refl _ theorem reverse_concat (s t : list T) : reverse (s ++ t) = (reverse t) ++ (reverse s) := list_induction_on s (symm (concat_nil _)) (take x s, assume IH : reverse (s ++ t) = concat (reverse t) (reverse s), calc reverse ((x :: s) ++ t) = reverse (s ++ t) ++ [x] : refl _ ... = reverse t ++ reverse s ++ [x] : {IH} ... = reverse t ++ (reverse s ++ [x]) : concat_assoc _ _ _ ... = reverse t ++ (reverse (x :: s)) : refl _) theorem reverse_reverse (l : list T) : reverse (reverse l) = l := list_induction_on l (refl _) (take x l', assume H: reverse (reverse l') = l', show reverse (reverse (x :: l')) = x :: l', from calc reverse (reverse (x :: l')) = reverse (reverse l' ++ [x]) : refl _ ... = reverse [x] ++ reverse (reverse l') : reverse_concat _ _ ... = [x] ++ l' : { H } ... = x :: l' : refl _) theorem append_eq_reverse_cons (x : T) (l : list T) : append x l = reverse (x :: reverse l) := list_induction_on l (refl _) (take y l', assume H : append x l' = reverse (x :: reverse l'), calc append x (y :: l') = (y :: l') ++ [ x ] : append_eq_concat _ _ ... = concat (reverse (reverse (y :: l'))) [ x ] : {symm (reverse_reverse _)} ... = reverse (x :: (reverse (y :: l'))) : refl _) -- Head and tail -- ------------- definition head (x0 : T) : list T → T := list_rec x0 (fun x l h, x) theorem head_nil (x0 : T) : head x0 (@nil T) = x0 := refl _ theorem head_cons (x : T) (x0 : T) (t : list T) : head x0 (x :: t) = x := refl _ theorem head_concat (s t : list T) (x0 : T) : s ≠ nil → (head x0 (s ++ t) = head x0 s) := list_cases_on s (take H : nil ≠ nil, absurd_elim (head x0 (concat nil t) = head x0 nil) (refl nil) H) (take x s, take H : cons x s ≠ nil, calc head x0 (concat (cons x s) t) = head x0 (cons x (concat s t)) : {cons_concat _ _ _} ... = x : {head_cons _ _ _} ... = head x0 (cons x s) : {symm ( head_cons x x0 s)}) definition tail : list T → list T := list_rec nil (fun x l b, l) theorem tail_nil : tail (@nil T) = nil := refl _ theorem tail_cons (x : T) (l : list T) : tail (cons x l) = l := refl _ theorem cons_head_tail (x0 : T) (l : list T) : l ≠ nil → (head x0 l) :: (tail l) = l := list_cases_on l (assume H : nil ≠ nil, absurd_elim _ (refl _) H) (take x l, assume H : cons x l ≠ nil, refl _) -- List membership -- --------------- definition mem (x : T) : list T → Prop := list_rec false (fun y l H, x = y ∨ H) infix `∈` : 50 := mem -- TODO: constructively, equality is stronger. Use that? theorem mem_nil (x : T) : x ∈ nil ↔ false := iff_refl _ theorem mem_cons (x : T) (y : T) (l : list T) : mem x (cons y l) ↔ (x = y ∨ mem x l) := iff_refl _ theorem mem_concat_imp_or (x : T) (s t : list T) : x ∈ s ++ t → x ∈ s ∨ x ∈ t := list_induction_on s (or_intro_right _) (take y s, assume IH : x ∈ s ++ t → x ∈ s ∨ x ∈ t, assume H1 : x ∈ (y :: s) ++ t, have H2 : x = y ∨ x ∈ s ++ t, from H1, have H3 : x = y ∨ x ∈ s ∨ x ∈ t, from imp_or_right H2 IH, iff_elim_right (or_assoc _ _ _) H3) theorem mem_or_imp_concat (x : T) (s t : list T) : x ∈ s ∨ x ∈ t → x ∈ s ++ t := list_induction_on s (take H, or_elim H (false_elim _) (assume H, H)) (take y s, assume IH : x ∈ s ∨ x ∈ t → x ∈ s ++ t, assume H : x ∈ y :: s ∨ x ∈ t, or_elim H (assume H1, or_elim H1 (take H2 : x = y, or_intro_left _ H2) (take H2 : x ∈ s, or_intro_right _ (IH (or_intro_left _ H2)))) (assume H1 : x ∈ t, or_intro_right _ (IH (or_intro_right _ H1)))) theorem mem_concat (x : T) (s t : list T) : x ∈ s ++ t ↔ x ∈ s ∨ x ∈ t := iff_intro (mem_concat_imp_or _ _ _) (mem_or_imp_concat _ _ _) theorem mem_split (x : T) (l : list T) : x ∈ l → ∃s t : list T, l = s ++ (x :: t) := list_induction_on l (take H : x ∈ nil, false_elim _ (iff_elim_left (mem_nil x) H)) (take y l, assume IH : x ∈ l → ∃s t : list T, l = s ++ (x :: t), assume H : x ∈ y :: l, or_elim H (assume H1 : x = y, exists_intro nil (exists_intro l (subst H1 (refl _)))) (assume H1 : x ∈ l, obtain s (H2 : ∃t : list T, l = s ++ (x :: t)), from IH H1, obtain t (H3 : l = s ++ (x :: t)), from H2, have H4 : y :: l = (y :: s) ++ (x :: t), from subst H3 (refl (y :: l)), exists_intro _ (exists_intro _ H4))) -- Find -- ---- -- to do this: need decidability of = for nat -- definition find (x : T) : list T → nat -- := list_rec 0 (fun y l b, if x = y then 0 else succ b) -- theorem find_nil (f : T) : find f nil = 0 -- :=refl _ -- theorem find_cons (x y : T) (l : list T) : find x (cons y l) = -- if x = y then 0 else succ (find x l) -- := refl _ -- theorem not_mem_find (l : list T) (x : T) : ¬ mem x l → find x l = length l -- := -- @list_induction_on T (λl, ¬ mem x l → find x l = length l) l -- -- list_induction_on l -- (assume P1 : ¬ mem x nil, -- show find x nil = length nil, from -- calc -- find x nil = 0 : find_nil _ -- ... = length nil : by simp) -- (take y l, -- assume IH : ¬ (mem x l) → find x l = length l, -- assume P1 : ¬ (mem x (cons y l)), -- have P2 : ¬ (mem x l ∨ (y = x)), from subst P1 (mem_cons _ _ _), -- have P3 : ¬ (mem x l) ∧ (y ≠ x),from subst P2 (not_or _ _), -- have P4 : x ≠ y, from ne_symm (and_elim_right P3), -- calc -- find x (cons y l) = succ (find x l) : -- trans (find_cons _ _ _) (not_imp_if_eq P4 _ _) -- ... = succ (length l) : {IH (and_elim_left P3)} -- ... = length (cons y l) : symm (length_cons _ _)) -- nth element -- ----------- definition nth (x0 : T) (l : list T) (n : ℕ) : T := nat_rec (λl, head x0 l) (λm f l, f (tail l)) n l theorem nth_zero (x0 : T) (l : list T) : nth x0 l 0 = head x0 l := refl _ theorem nth_succ (x0 : T) (l : list T) (n : ℕ) : nth x0 l (succ n) = nth x0 (tail l) n := refl _ end -- declare global notation outside the section infixl `++` : 65 := concat end list